Medieval Canon Lawyers and European Legal Tradition. A Brief Overview - Giaro, Tomasz (Review of European and Comparative Law, 2021)
The Roman Church was a leading public institution of the Middle Ages and its law, canon law, belonged to most powerful factors of European legal history. Today’s lawyers have hardly any awareness of the canonist origins of several current legal institutions. Together with Roman law, canon law constituted the system of “both laws” (utrumque ius) which were the only laws acknowledged as “learned” and, consequently, taught at medieval universities. The dualism of secular (imperium) and spiritual power (sacerdotium), symbolized by so-called two swords doctrine, conferred to the Western legal tradition its balance and stability. We analyze the most important institutional achievements of the medieval canon lawyers: acquisitive prescription, the Roman-canonical procedure, the theory of just war, marriage and family law, freedom of contract, the inheritance under will, juristic personality, some institutions of constitutional law, in particular those based on the concept of representation, and finally commercial law. Last not least, the applicability of canon law defined the territorial extension of medieval and early modern Christian civilization which exceeded by far the borders of the Holy Roman Empire, where Roman law was effective as the law of the ruler. Hence, the first scholar to associate Roman law with (continental) Europe as a relatively homogeneous legal area, Paul Koschaker, committed in his monograph Europa und das römische Recht, published in 1947, the error of taking a part for the whole. In fact, Western legal tradition was based, in its entirety, not on Roman, but rather on canon law; embracing the common law of England, it represented – to cite Harold Joseph Berman – the first great “transnational legal culture”. At the end, some structural features of canon law are discussed, such as the frequent use of soft-law instruments and the respect for tradition, clearly visible in the approach to the problem of codification.